Targeted Codelivery of Prodigiosin and Simvastatin Using Smart BioMOF: Functionalization by Recombinant Anti-VEGFR1 scFv - Mirzaeinia, Somayyeh; Zeinali, Sedighe; Budisa, Nediljko; Karbalaei-Heidari, Hamid Reza (Frontiers in Bioengineering and Biotechnology, 2022)
Biological metal-organic frameworks (BioMOFs) are hybrid compounds in which metal nodes are linked to biocompatible organic ligands and have potential for medical application. Herein, we developed a novel BioMOF modified with an anti-VEGFR1 scFv antibody (D16F7 scFv). Our BioMOF is co-loaded with a combination of an anticancer compound and a lipid-lowering drug to simultaneously suppress the proliferation, growth rate and metastases of cancer cells in cell culture model system. In particular, Prodigiosin (PG) and Simvastatin (SIM) were co-loaded into the newly synthesized Ca-Gly BioMOF nanoparticles coated with maltose and functionalized with a recombinant maltose binding protein-scFv fragment of anti-VEGFR1 (Ca-Gly-Maltose-D16F7). The nanoformulation, termed PG+SIM-NP-D16F7, has been shown to have strong active targeting behavior towards VEGFR1-overexpresing cancer cells. Moreover, the co-delivery of PG and SIM not only effectively inhibits the proliferation of cancer cells, but also prevents their invasion and metastasis. The PG+SIM-NP-D16F7 nanocarrier exhibited stronger cytotoxic and anti-metastatic effects compared to mono-treatment of free drugs and drug-loaded nanoparticles. Smart co-delivery of PG and SIM on BioMOF nanoparticles had synergistic effects on growth inhibition and prevented cancer cell metastasis. The present nanoplatform can be introduced as a promising tool for chemotherapy compared with mono-treatment and/or non-targeted formulations.